Farmers’ Adaptation to Climate Change: A Review on Strategies and Influencing Factors - Sofia Rizkya Maulidani (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2026)
Climate change poses significant challenges to the agricultural sector, particularly in regions where farming practices are closely tied to environmental conditions. Farmers are increasingly required to adapt to unpredictable climatic shifts that threaten crop productivity, land quality, and food security. This study aims to explore the various strategies employed by farmers to adapt to climate change, as well as the factors influencing their adaptability. Using a qualitative literature review methodology, the study synthesizes findings from multiple sources to identify key behavioral, technological, and institutional components of adaptation. The analysis reveals that farmers’ adaptation strategies are shaped by their experience, knowledge, perceptions, access to technology, and support from government and community institutions. Adaptation occurs both physically, through changes in cropping patterns and infrastructure, and socially, through education, group activities, and policy interventions. However, limited access to training and resources continues to hinder effective adaptation in many contexts. The findings underscore the importance of integrated support systems and targeted policy measures to enhance farmers’ resilience to climate change. Strengthening adaptive capacity at the farm level is essential for safeguarding agricultural sustainability and ensuring food security in the face of environmental uncertainty.